The Identify The Influence Of Coffee Brewing Techniques on Coffee Quality - Maya Zevanya Manurun (Yayasan Rahmatan Fiddunya Wal Akhirah, 2025)
Coffee is one type of plantation crop that is widely cultivated in the world. From In 1980-2013, the growth rate of coffee plant productivity in the world continued to experience increase with an average growth of 2.21%. This research aims to identify the effect of coffee brewing techniques on the quality of the taste of the coffee produced. Several brewing techniques commonly used in the coffee industry, such as the siphon, pour-over, French press, and espresso methods, have different characteristics in the process of extracting chemicals from coffee beans. Different brewing techniques are expected to produce significant differences in the taste, aroma, acidity, viscosity and caffeine content of coffee